Effect of nanoparticles synthesized from green extracts on dark fermentative biohydrogen production - Yildirim, Oznur; Ozkaya, Bestami (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Research on the production of nanoparticles with sustainable methods using different leaf extracts as a reducing agent has gained momentum. In this study, green synthesis of two types of iron oxide nanoparticles were produced to investigate the impact of nanoparticles on bio-hydrogen yield. Olive leaf extract and microalgae extract were used as reducing agents for production. The synthesized nanoparticles were characterized via SEM, EDX, XRD and UV-Visible spectrum analyses. The nanoparticles have a stable appearance and mean particle sizes of 90.26 and 124.68 nm. Iron oxide nanoparticles produced from olive leaf extract were more effective in dark fermentation. Dark fermentation yields by Clostridium sp. were assessed utilizing various proportions of generated two types of nanoparticles (50-400 mg/L). The addition of 200 mg/L olive leaf extract-based iron oxide nanoparticles and 300 mg/L microalgae extract-based iron oxide nanoparticles enhanced the hydrogen production capacity by 41% and 28%, respectively.
Keywords: Iron oxide nanoparticle; Bio-hydrogen; Microalgae; Olive leaf; HYDROGEN-PRODUCTION; OXIDE NANOPARTICLES; IRON NANOPARTICLES; NICKEL NANOPARTICLES; SCHERRER EQUATION; ENHANCEMENT; METAL; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels